A Case Series on the Use of Dupilumab for Treatment of Refractory Eosinophilic Gastrointestinal Disorders. Issue 2 (6th June 2022) - Patel, Naiya; Goyal, Aakash; Thaker, Ameet; Troendle, David; Parrish, Christopher
Abstract : The incidence and prevalence of eosinophilic esophagitis (EoE), eosinophilic gastritis (EoG), eosinophilic enteritis (EoN), and eosinophilic colitis (EoC) are increasing (1 ). These conditions will inevitably become more widely recognized and better understood. There is currently no Food and Drug Administration (FDA)–approved treatment for EoE, but there are standard-of-care treatments that are well established and widely used. In contrast, there is a paucity of data regarding standard-of-care treatment for non-EoE eosinophilic gastrointestinal disorders (EGID). We identified 3 patients that all achieved clinical and histopathologic remission on dupilumab, a monoclonal antibody that blocks the downstream signaling of interleukin (IL)-4 and IL-13. These patients had extra-esophageal forms of EGID with two patients failing to achieve remission on standard-of-care therapies and one patient experiencing significant side effects on swallowed budesonide therapy. The reduction in mucosal eosinophilia in several GI tract segments in these 3 patients highlights a new potential clinical indication for dupilumab in the treatment of pediatric EGID patients.